Ballerina [videorecording (DVD)] - Hatten, Shay; Armas, Ana de, 1988-; Huston, Anjelica; Byrne, Gabriel, 1950-; Reddick, Lance; Sandino Moreno, Catalina, 1981-; Reedus, Norman, 1969-; McShane, Ian, 1942-; Reeves, Keanu; McCarthy, Ava Joyce; Lacourbas, Romain; Kalivas, Tina; et al. (Lionsgate, 2025)
"The next chapter from the world of John Wick follows Eve Macarro, who is beginning her training in the assassin traditions of the Ruska Roma. Eve seeks revenge for her father's death, and finds herself crossing paths with John Wick himself."--